Hubungan obesitas dan aktivitas fisik dengan kejadian diabetes melitus tipe II pada usia > 40 tahun di wilayah kerja Puskesmas Bukit Hindu - Haryono, Diajeng Akbar; Arifin, Syamsul; Shinta, Herlina Eka; Widodo, Tri; Yuliani, Ni Nyoman Sri (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Diabetes Mellitus is a group of metabolic diseases with characteristics of hyperglycemia. International Diabetes Federation estimates that 9.3% of the total population in the world and 10.7 million people in Indonesia suffered from diabetes mellitus in 2019. The incidence of diabetes mellitus in Central Kalimantan is still quite high, where the city of Palangka Raya with the most cases of diabetes mellitus occurred at the Bukit Hindu Health Center. The aim is to determine the relationship of obesity and physical activity with the incidence of diabetes mellitus type II at the age of > 40 years in the Working Area of Bukit Hindu Health Center. Using observational analytic method with cross sectional approach. Sampling using purposive sampling technique, with the number of respondents aged > 40 years as many as 40 respondents. Data collection using primary data through interviews using questionnaires and measurements of weight and height. Statistical test using chi square test (α < 0,05). Result data analysis with univariate and bivariate analysis. Bivariate analysis found that obesity variable has a relationship with the occurrence of diabetes mellitus type II (p-value 0.005) and physical activity variable also has a relationship with the occurrence of diabetes mellitus type II (p-value 0.001). There is a relationship of obesity and physical activity with the occurrence of diabetes mellitus type II at the age of > 40 years in the working area of Bukit Hindu Health Center.